LITHIUM-ION BATTERIES AND SOLAR CELLS; PHYSICAL, CHEMICAL, AND MATERIALS PROPERTIES - Lin, Ming-Fa; Hsu, Wen-Dung; Huang, Jow-Lay (BOCA RATON : CRC PRESS, 2021)
Lithium-Ion Batteries and Solar Cells: Physical, Chemical, and Materials Properties presents a thorough investigation of diverse physical, chemical, and materials properties and special functionalities of lithium-ion batteries and solar cells. It covers theoretical simulations and high-resolution experimental measurements that promote a full understanding of the basic science to develop excellent device performance. Employs first-principles and the machine learning method to fully explore the rich and unique phenomena of cathode, anode, and electrolyte (solid and liquid states) in lithium-ion batteries Develops distinct experimental methods and techniques to enhance the performance of lithium-ion batteries and solar cells Reviews syntheses, fabrication, and measurements Discusses open issues, challenges, and potential commercial applications This book is aimed at materials scientists, chemical engineers, and electrical engineers developing enhanced batteries and solar cells for peak performance.
Diverse phenomena in stage-n graphite alkali-intercalation compounds / Wei-bang Lin, Ngoc Thanh Thuy Tran, Shih-yang Lin -- Effect of Nitrogen doping on the Li storage capacity of graphene nanomaterials : A first-principles study / Yu-Jen Tsai and Chin-Lung Kuo -- Fundamental properties of Li+-based battery anode : Li4Ti5O12 / Thi Dieu Hien Nguyen, Hai Duong Pham, Shih-Yang Lin, Ngoc Thanh Thuy Tran, and Ming-Fa Lin.
OCLC-licensed vendor bibliographic record.
Keywords: Lithium ion batteries -- Materials; Solar cells -- Materials; TECHNOLOGY / Material Science; TECHNOLOGY / Power Resources